A study of serum calcium, phosphorous and magnesium level in hypothyroid cases (Journal of Pathology of Nepal, 2022)
Background: Hypothyroidism is an endocrine disorder occurred either due to its impaired activity or hormonal deficiency. Trace elements are required as a cofactor for many enzymes in various metabolic pathways which are regulated by thyroid hormone. Hence, thyroid disorders are linked with disturbances in various metabolisms. So, the purpose of this study is to evaluate whether serum calcium, magnesium, and phosphorus level are deranged or not in hypothyroid cases.Materials and Methods: A prospective study was carried out in a total of 112 cases of hypothyroid and euthyroid subjects aged 20-50 years involving both male and female individuals. Thyroid function test, serum calcium, phosphorous and magnesium activities were measured in both the study population.Results: Serum calcium was significantly lower while serum phosphorous and magnesium levels were significantly higher in hypothyroidism (p